POLYCYSTIC OVARY SYNDROME: PATHOGENESIS, TREATMENT AND SECONDARY ASSOCIATED DISEASES: POLYCYSTIC OVARY SYNDROME: PATHOGENESIS, TREATMENT AND SECONDARY ASSOCIATED DISEASES - Soni, Abhishek; Singla, Shivali; Goyal, Sachin (Journal of Drug Delivery and Therapeutics, 2018)
Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age. It is characterized by hyperandrogenism, polycystic ovaries, and chronic anovulation along with insulin resistance, hyperinsulinemia, abdominal obesity, hypertension, and dyslipidemia as frequent metabolic traits (metabolic syndrome) that culminate in serious long-term consequences such as type 2 diabetes mellitus, endometrial hyperplasia, and coronary artery disease. It is one of the most common causes of anovulatory infertility. A complete understanding of the underlying Pathophysiology of PCOS is still lacking. Because of the heterogeneity of this disorder, there are most likely multiple underlying pathophysiologic mechanisms. Pathogenesis of PCOS is explaining as alteration in gonadotropin-releasing hormone secretion results in increased luteinizing hormone (LH) secretion. An alteration in insulin secretion and insulin action results in hyperinsulinemia and insulin resistance. A defect in androgen synthesis that results in increased ovarian androgen production.Treatment of PCOS include maintaining a normal endometrium, antagonizing the actions of androgens on target tissues, reducing insulin resistance (when present), and correcting anovulation. Women with polycystic ovary syndrome (PCOS) are at higher risk for several other health conditions as Insulin Resistance, Metabolic Syndrome, Type 2 Diabetes, Obesity, Heart Disease and High Blood Pressure (Cardiovascular Disease)